Diseño y construcción de un banco de pruebas didáctico para la caja de transmisión mecánica de un vehículo de gama baja para el laboratorio de mecánica de la Universidad Antonio Nariño (2023)
The profile of a modern engineer requires not only solid theoretical knowledge, but also the ability to address challenges in mechanical systems that convert or transmit motion from their generating sources. These skills include the ability to work in teams, synthesis of information, handling of specialized tools and creativity to solve problems.